Bài 84 trang 156 SGK Đại số 10 nâng cao


    Giải các phương trình saua) \(|x^2– 2x – 3| = 2x + 2\)b) \(\sqrt {{x^2} - 4}  = 2(x - \sqrt 3 )\)Đáp ána) Điều kiện: \(x ≥  -1\). Ta có:\(\eqalign{ & \left| {{x^2}-2x-3} \right| = 2x + {\rm{ }}2\cr& \Leftrightarrow \left[ \matrix{ {x^2}-2x-3 = 2x + 2 \hfill \cr...

    Giải các phương trình sau

    a) \(|x^2– 2x – 3| = 2x + 2\)

    b) \(\sqrt {{x^2} – 4}  = 2(x – \sqrt 3 )\)

    Đáp án

    a) Điều kiện: \(x ≥  -1\). Ta có:

    \(\eqalign{
    & \left| {{x^2}-2x-3} \right| = 2x + {\rm{ }}2\cr& \Leftrightarrow \left[ \matrix{
    {x^2}-2x-3 = 2x + 2 \hfill \cr
    {x^2}-2x-3 = – 2x – 2 \hfill \cr} \right. \cr
    & \Leftrightarrow \left[ \matrix{
    {x^2} – 4x – 5 = 0 \hfill \cr
    {x^2} – 1 = 0 \hfill \cr} \right. \Leftrightarrow \left[ \matrix{
    x = – 1;\,x = 5 \hfill \cr
    x = \pm 1 \hfill \cr} \right. (\text{nhận})\cr} \)

    Vậy S = {-1, 1, 5}

    b) Ta có:

    \(\sqrt {{x^2} – 4} = 2(x – \sqrt 3 )\)

    \(\Leftrightarrow \left\{ \matrix{
    x \ge \sqrt 3 \hfill \cr
    {x^2} – 4 = 4({x^2} – 2\sqrt 3 + 3) \hfill \cr} \right. \)

    \(\Leftrightarrow \left\{ \matrix{
    x \ge \sqrt 3 \hfill \cr
    3{x^2} – 8\sqrt 3 + 16 = 0 \hfill \cr} \right.\) 

    Vậy \(S = {\rm{\{ }}{{4\sqrt 3 } \over 3}{\rm{\} }}\)